Halal Industry in Indonesia: The Role of Sharia Financial Institutions in Driving Industrial and Halal Ecosystem - Rachman, M. Aulia; Syamsuddin, Syamsuddin (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
t. Halal market has emerged as a sector of new development and creating market potential in the global economy. Sharia Financial Institutions (SFI) has an important role as an intermediation between unit deficits and surpluses in the economy with sharia principles. As the development of halal products and industries make SFI have an important role in encouraging the growth, literacy and potential of the halal industry. This paper presents the ideas and roles of SFI in encouraging the potential of halal industry in Indonesia. Using qualitative descriptive approach, this paper finds out that there is still unbalance between the availability of products, demands, markets and the structure of halal industrial institutions. The halal certification efforts are still focused on food, medicines, and sharia financial institutions. Products related to tourism industries and information media remain untouched. Pasar produk halal muncul sebagai sektor pembangunan baru dan telah menciptakan pasar potensial dalam ekonomi global. Lembaga Keuangan Syariah (LKS) memiliki peranan penting untuk menjembatani antara unit defist dan surplus dalam praktek ekonomi syariah. Artikel ini bertujuan untuk memberikan gambaran mengenai potensi, prospek dan literasi terkait dengan industri halal di Indonesia; dan peran LKS dalam mendorong tumbuhnya ekosistem dan industri halal. Dengan menggunakan metode kualitatif deskriptif, kajian ini menemukan bahwa potensi yang besar pada industri halal masih perlu dikembangkan dan didukung oleh pemangku kepentingan terkait. Masih ada ketidakseimbangan antara produk, permintaan, pasar dan stuktur kelembagaan dalam industri halal. Terkait dengan jaminan halal, upaya sertifikasi halal masih difokuskan pada produk-produk makanan, obatobatan dan LKS, sementara produk terkait dengan industri pariwisata dan media informasi masih belum tersentuh.